2015
DOI: 10.2147/idr.s55778
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and food animals as a source of antimicrobial-resistant bacteria

Abstract: One of the major breakthroughs in the history of medicine is undoubtedly the discovery of antibiotics. Their use in animal husbandry and veterinary medicine has resulted in healthier and more productive farm animals, ensuring the welfare and health of both animals and humans. Unfortunately, from the first use of penicillin, the resistance countdown started to tick. Nowadays, the infections caused by antibiotic-resistant bacteria are increasing, and resistance to antibiotics is probably the major public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
456
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(477 citation statements)
references
References 112 publications
(137 reference statements)
4
456
0
17
Order By: Relevance
“…The presence of AMR bacteria in borehole water has been attributed to the indiscriminate use of antibiotics, especially in animal husbandry, coupled with human practices, such as improper sanitation and discharge of human wastes in the environment (8,41). These result in the creation of ecological niches, which serve as pools of resistance, to which bacteria can pick up antimicrobial resistance genes (41). Meanwhile, most of the bacterial isolates in this study showed multidrug resistance to at least six antibiotics.…”
Section: Microbiological Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…The presence of AMR bacteria in borehole water has been attributed to the indiscriminate use of antibiotics, especially in animal husbandry, coupled with human practices, such as improper sanitation and discharge of human wastes in the environment (8,41). These result in the creation of ecological niches, which serve as pools of resistance, to which bacteria can pick up antimicrobial resistance genes (41). Meanwhile, most of the bacterial isolates in this study showed multidrug resistance to at least six antibiotics.…”
Section: Microbiological Analysismentioning
confidence: 80%
“…In one such study, Ateba et al reported the presence of isolates that were resistant to chloramphenicol, vancomycin, oxytetracycline, amoxicillin, erythromycin, and sulfamethoxazole (8). The presence of AMR bacteria in borehole water has been attributed to the indiscriminate use of antibiotics, especially in animal husbandry, coupled with human practices, such as improper sanitation and discharge of human wastes in the environment (8,41). These result in the creation of ecological niches, which serve as pools of resistance, to which bacteria can pick up antimicrobial resistance genes (41).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Some diseases that were previously considered dreadful for centuries have been successfully treated or controlled by means of antibiotics [8]. In addition, antibiotics have also been used extensively at subtherapeutic levels as growth promoter/feed enhancer in livestock farming, most especially in the industrialised nations, including many European countries and the United States of America [9][10][11][12]. However, the spontaneous emergence and spread of antibiotic resistance, coupled with diminished numbers of novel antibiotics, has threatened the feat of antibiotics in modern medicine, and induced the fear of a possible post-antibiotic era [13].…”
Section: Introductionmentioning
confidence: 99%
“…Use of antibiotics in food-animal agriculture is thought to contribute to the emergence and amplification of antibiotic-resistant strains of Salmonella (Economou and Gousia, 2015). Although, several published reports illustrate how antibiotic-resistant (ABR) bacteria isolated from food animals overlaps with those causing human infection including foodborne illness (Li et al, 2013;Marshall and Levy, 2011), non-overlap trends of antibiotic resistance infections between humans and animals are also reported (Mather et al, 2012).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%
“…Meat, including goat meat, is an important source of protein but also can serve as a potential source of foodborne pathogens (Economou and Gousia, 2015).…”
Section: Introductionmentioning
confidence: 99%